Stabreim und Endreim - Groenke, Ulrich (Folia Scandinavica Posnaniensia, 2007)
The remnants of ancient German alliterating poetry that have come down to us are sparse. In the middle of the 9th century alliterating poetry had practically come to an end in the High German language area. At the same time an extensive Christian literature made its appearance (Otfried), using almost exclusively end rhyme. In accordance with the prevalent philological opinion that end rhyme harmonizes perfectly with the concept of Christianity. It was the ideal vehicle for communicating Christian flights of fancy, which alliterating rhyme was not. Alliteration, therefore, yields to end rhyme. In the light of a of Icelandic poetry this view cannot be shared. Christian poetry, be it Scaldic art (e.g. Lilja), be it baroque art (e.g. Passiusalmar), conveys its message harmoniously using a strict alliteration pattern with end rhyme. The alliterating end rhyme verse is the typical pattern of Icelandic poetry, with its earliest appearance in early Scaldic poetry. - An appendix to this article treats alliterating end rhyme verse in Finnish literature.